Current review of conections between lichen planus and mental disorders - Krystian Cholewa; Kinga Mitas; Bartłomiej Zaremba; Klaudia Artykiewicz; Magdalena Kozyra; Joanna Milanowska (Kazimierz Wielki University, 2020)
The major aim of this article was to examine causal connection or temporal relation between mental disorders and lichen planus (LP). LP is a chronic, inflammatory skin condition affecting less than 1% of the adult population. It is observed in many different clinical forms, some affecting more psychical state than others. Indeed, connection exist between LP and mental state. LP as an autoimmune disease can also be aggravated by psychosocial stressors. Etiopatogenesis of LP is idiopathic and involves immunologic components. Main pathogenetic mechanism of LP include increased apoptosis of keratinocytes and decreased apoptosis of T-cells. Many authors report relationship LP between mental illness like depression and anxiety disorder or lack of emotional stability. One of the main symptoms of LP is is severe itch (present in 74 from 78 patients), which can be induced by stress.